2017
DOI: 10.1128/aac.02292-16
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring of nfxB Mutant Occurrence and Dynamics in Pseudomonas aeruginosa Biofilm Exposed to Subinhibitory Concentrations of Ciprofloxacin

Abstract: Biofilm infections caused by Pseudomonas aeruginosa are frequently treated with ciprofloxacin (CIP); however, resistance rapidly develops. One of the primary resistance mechanisms is the overexpression of the MexCD-OprJ pump due to a mutation in nfxB, encoding the transcriptional repressor of this pump. The aim of this study was to investigate the effect of subinhibitory concentrations of CIP on the occurrence of nfxB mutants in the wild-type PAO1 flow cell biofilm model. For this purpose, we constructed fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…In addition, ciprofloxacin is excreted in sweat and present on the skin at low concentrations for long periods of time (22), with rapid development of resistance in skin bacteria. Therefore, it is relevant to address the role of subinhibitory concentrations of ciprofloxacin in the development of resistance, and we have already published a study on the fast development of resistance in planktonic experimental evolution (23) and in flow cell biofilms using a monitor for mutations in nfxB, the negative regulator of the MexCD-OprJ efflux pump (24); similar findings were reported by Macià et al (25).…”
supporting
confidence: 70%
“…In addition, ciprofloxacin is excreted in sweat and present on the skin at low concentrations for long periods of time (22), with rapid development of resistance in skin bacteria. Therefore, it is relevant to address the role of subinhibitory concentrations of ciprofloxacin in the development of resistance, and we have already published a study on the fast development of resistance in planktonic experimental evolution (23) and in flow cell biofilms using a monitor for mutations in nfxB, the negative regulator of the MexCD-OprJ efflux pump (24); similar findings were reported by Macià et al (25).…”
supporting
confidence: 70%
“…Furthermore, a majority of these mutations were in genes that are not typical resistance genes (i.e., cyoB , nuoG , trkH , and znuA ). This finding raises the question if a substantial “dark matter” of unknown resistance mutations for other classes of antibiotics exists in clinical isolates that apart from the generally easily identified bona fide resistance genes/mutations may be involved in resistance evolution and make a significant contribution to the clinical resistance phenotype 14 , 18 , 19 , 56 . Thus, it is conceivable that the initial selection for common mutations of small effect could act as a stepping stone for the subsequent occurrence of a rarer large effect genetic event (e.g., horizontal gene transfer of a bona fide resistance gene) and thereby act as a driver of resistance evolution.…”
Section: Discussionmentioning
confidence: 99%
“…While many studies have examined the genetics of mutational antibiotic resistance selected at high levels (>MIC) of antibiotics, less is known about the effects of long-term exposure to low levels (<MIC) of antibiotics 14 19 . When susceptible bacteria are exposed to antibiotic concentrations above the MIC they will die or stop growing, and only bacteria where resistance mutations were present prior to antibiotic exposure will be able to grow.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, biofilm-related infections are more difficult to clear and more prone to relapse (Koo, Allan, Howlin, Stoodley, & Hall-Stoodley, 2017). Notably, some studies have demonstrated that biofilm formation is increased in response to subinhibitory concentrations of antibiotics, which is typically a direct consequence of low-dose therapy, indicating that biofilm regulation is involved in the global response to external stresses, such as antibiotics (Kaplan, 2011;Zaborskyte, Andersen, Kragh, & Ciofu, 2017). However, the correlation between the biofilm formation ability of A. baumannii and antibiotic resistance remains unclear.…”
mentioning
confidence: 99%